2017
DOI: 10.1002/ijch.201700105
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbituril As A Versatile Tool to Tune the Functions of Proteins

Abstract: Tuning the functions of proteins is a key issue in chemistry and biochemistry. The modification of proteins by chemical or biological methods is proven to be a classical method that allows proteins to achieve multiple functions. Compared with traditional methods, cucurbiturils as a new series of macrocyclic supramolecular hosts have been explored to modify and control protein functions because they could recognize and bind to short aromatic peptide sequences specifically. After guest molecules are incorporated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…DNA (100 μL; 0.1 mg/mL) was added to 1 mL of DA (50 mg/mL) or CB–DA (50 mg/mL), and the surface charges of the DA–DNA and CB–DA–DNA mixtures after washing out the free DNA are shown in Figure 5C. The reduction in the surface charge of the CB–DA–DNA indicates that the CB–DA composite is more effective at capturing the nucleic acid, and this effect may be due to the previously reported covalent bonding, physical adsorption, electrostatic interactions, and heterogeneous surface binding intrinsic to supermolecular family members [23,24].…”
Section: Resultsmentioning
confidence: 87%
“…DNA (100 μL; 0.1 mg/mL) was added to 1 mL of DA (50 mg/mL) or CB–DA (50 mg/mL), and the surface charges of the DA–DNA and CB–DA–DNA mixtures after washing out the free DNA are shown in Figure 5C. The reduction in the surface charge of the CB–DA–DNA indicates that the CB–DA composite is more effective at capturing the nucleic acid, and this effect may be due to the previously reported covalent bonding, physical adsorption, electrostatic interactions, and heterogeneous surface binding intrinsic to supermolecular family members [23,24].…”
Section: Resultsmentioning
confidence: 87%
“…Kinetic results for 4-methylbenzylammonium ion assembly with cucurbit [6]uril (CB6) demonstrated the existence of both exclusion and inclusion complexes. 57 Nau and coworkers suggested that primary ammonium cations first bind to the portal of CB6 producing an exclusion complex in which the organic moiety is still located in the bulk solvent.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The capability of synthetic host compounds to recognize amino acids, peptides, and protein surface elements can be used to modulate the interactions between proteins and to modify the activity of biomolecules. 5,6 Among water-soluble biocompatible hosts, cucurbiturils (CBn) and their acyclic analogues have attracted particular attention due to their remarkable binding capability. [7][8][9][10] The confinement in this type of molecular container improved the solubility, stability and bioactivity of guest molecules, [11][12][13][14] which can be exploited to develop novel drug formulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dendrimers and proteins have be reported as building blocks for the construction of supramolecular polymers by other host–guest interactions. Wang and Kaifer reported that viologen‐containing dendrimers could be efficiently dimerized by one‐electron reduction in the presence of a CB[8] host .…”
Section: Cucurbit[8]uril‐based Polymersmentioning
confidence: 99%